2017
DOI: 10.24840/2184-0954_001.001_0008
|View full text |Cite
|
Sign up to set email alerts
|

Indoor radon levels and total gamma dose rates measurements in Portuguese thermal spas

Abstract: In this study, an assessment of indoor radon concentration and gamma dose rates were carried out in 16 Portuguese thermal spas. Indoor gamma dose rates measurements were made using a Geiger counter (Gamma Scout -GS3) and radon concentration measurements were carried out using CR-39 detectors. The detectors were exposed for an extended period of time (in average 42 days). The results showed that gamma doses rates are generally low but, in several cases, radon concentration exceeded national as well as internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In this thermal bath, no storage reservoirs for water are present, unlike in other modern spas. The 222 Rn concentrations are significantly higher when compared with those observed in modern spas elsewhere (see Table 1: Sohrabi, 1997;Radoli c et al, 2005;Song et al, 2005;Beitollahi et al, 2007;R odenas et al, 2008;Bituh et al, 2009;Onishchenko et al, 2010;Nikolov et al, 2012;Pugliese et al, 2013;Kasi c et al, 2015;M} ullerov a et al, 2016;Uzun and Demir€ oz, 2016;Karakaya et al, 2017;Silva and Dinis, 2017;Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…In this thermal bath, no storage reservoirs for water are present, unlike in other modern spas. The 222 Rn concentrations are significantly higher when compared with those observed in modern spas elsewhere (see Table 1: Sohrabi, 1997;Radoli c et al, 2005;Song et al, 2005;Beitollahi et al, 2007;R odenas et al, 2008;Bituh et al, 2009;Onishchenko et al, 2010;Nikolov et al, 2012;Pugliese et al, 2013;Kasi c et al, 2015;M} ullerov a et al, 2016;Uzun and Demir€ oz, 2016;Karakaya et al, 2017;Silva and Dinis, 2017;Wang et al, 2017).…”
Section: Resultsmentioning
confidence: 90%
“…Since the water source is the same for the baths and thermal pools, the concentration of 226 Ra fell approximately within the same range. If these values are compared with the results shown in Table 1 in which the reported indoor radon and 226 Ra activity concentrations in water in various spas around the world are presented, it can be seen that the concentration of this radionuclide is elevated compared to typical levels in surface waters (Radoli c et al, 2005;Song et al, 2005;Beitollahi et al, 2007;R odenas et al, 2008;Bituh et al, 2009;Onishchenko et al, 2010;Nikolov et al, 2012;Pugliese et al, 2013;Kasi c et al, 2015;M} ullerov a et al, 2016;Uzun and Demir€ oz, 2016;Karakaya et al, 2017;Silva and Dinis, 2017;Wang et al, 2017) but similar to radium levels in other spas.…”
Section: Resultsmentioning
confidence: 91%
“…They are produced by disintegration of 226 Ra and 224 Ra, respectively. Being inert gases, 222 Rn and 220 Rn are not affected by chemical processes and their concentrations in indoor atmospheres are strongly influenced by geological, geophysical, and atmospheric conditions (Anastasiou et al 2003;Kávási et al 2006;Lévesque et al 1997;Silva and Dinis 2017;Xie et al 2015;). As a result of the disintegration of 222 Rn and 220 Rn present in indoor atmospheres, solid isotopes of polonium ( 218 Po, 214 Po, 216 Po, and 212 Po), lead ( 214 Pb, 212 Pb), bismuth ( 214 Bi, 212 Bi), and thallium ( 208 Tl) are formed.…”
mentioning
confidence: 99%
“…222 Rn, 220 Rn, and their progeny are present in the air of dwellings and workplaces (Dehnert et al 2020;Sharma et al 2018;Singh et al 2015;ICRP 1993;Prasad et al 2016;Yu et al 1997;Ha et al 1999;UNSCEAR 1993;Misdaq et al 2015a). According to previous works, it has been shown that concentration levels of 222 Rn, 220 Rn and their progeny are significantly increased when pollutants are present in indoor air such as cigarette smoke (Misdaq and Flata 2003), thermal water vapor (Nikolopoulos et al, 2010;Silva and Dinis 2017;Misdaq et al 2012), marble dusts (Misdaq et al 2019), and petrol and gas-oil exhaust fumes (Misdaq et al 2015a). To assess radiation exposure for workers inside spa rooms, one should measure concentrations of 222 Rn,220 Rn, and their progeny in the air of these rooms.…”
mentioning
confidence: 99%